Peran Statistik Administrasi Dalam Evaluasi Kebijakan Publik: Studi Literatur - Mozin, Sri Yulianty; Dumbela, Utamy S.; Lestari, Dea Ayu; Ramadhani, Rini; Noho, Nurul Nazwa (JPS: Journal of Publicness Studies, 2025)
Administrative statistics play an important role in evaluating public policies, especially in measuring the effectiveness and efficiency of policy implementation. With accurate data and proper analysis, policymakers can make evidence-based decisions to improve public welfare. This study aims to examine the role of administrative statistics in the policy evaluation process. The method used in this study is a literature study with a descriptive-analytical approach. The results of the study indicate that administrative statistics contribute to the collection of relevant data, policy monitoring, and policy improvement based on empirical findings.